Production of fermentable sugar from Brown seaweed with optimization of chemical and enzymatic hydrolysis - Wong, Soon Thian (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
The carbohydrates present in brown seaweed are mainly laminarin and glucans (polysaccharide composed of glucose) such as cellulose. Saccharification is necessary to be performed in order to reduce the crystalinity of cellulose and degrading its intermolecular bonds, thus fermentable sugars is liberated. Saccharification process are carried out by both acid hydrolysis and enzymatic hydrolysis methods and they are complementary. In this research, the parameters that were optimized in acid hydrolysis included the reaction temperature, brown seaweed biomass concentration and sulfuric acid concentration. Meanwhile for enzymatic hydrolysis, the parameters that were optimized included reaction temperature and cellulase enzyme dosage. For both the process, the glucose concentration was analyzed by using Dinitrosalycylic acid (DNS) reagent. The optimization has been carried out by using Central Composite Design (CCD) to analyze the effect of the combination factor toward the response glucose concentration with the aid of Design Expert version 7.1.5 software. The optimum condition for acid hydrolysis were reaction temperature 100.0 C, biomass concentration 3.00 % (w/v) and sulfuric acid concentration 0.10 % (v/v) meanwhile for enzymatic hydrolysis were reaction temperature 45.0 C and enzyme dosage 0.02 mL per 0.30 g biomass. The results shown the highest sugar yield from acid hydrolysis and enzymatic hydrolysis were 3.465 g/L and 6.235 g/L respectively. Under optimized condition, it was examined that both acid and enzymatic would contribute 2.659 g/L and 3.159 g/L respectively to the total glucose yield 5.818 g/L.